2006
DOI: 10.1007/s11427-006-2037-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quercetin on chronic enhancement of spatial learning and memory of mice

Abstract: In this study we evaluated the effect of quercetin on D-galactose-induced aged mice using the Morris water maze (MWM) test. Based on the free radical theory of aging, experiments were performed to study the possible biochemical mechanisms of glutathione (GSH) level and hydroxyl radical (OH-) in the hippocampus and cerebral cortex and the brain tissue enzyme activity of the mice. The results indicated that quercetin can enhance the exploratory behavior, spatial learning and memory of the mice. The effects relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…These results provide evidence of the positive effect of onion extract on PON1 activity and prevention of LDL oxidation during periods of oxidative insult, with improvement in the antioxidant capability of rats, suggesting its value as a dietary antioxidant food . Moreover, quercetin has been previously shown to exert protective effects on ageing of specific tissues in mouse and other cellular models . Quercetin and its derivative, namely quercetin caprylate as a proteasome activator with antioxidant properties has been reported to influence cellular lifespan, survival and viability of Human foetal lung fibroblast, cell lines derived from a 16–18 week old human foetus (HFL‐1) primary human fibroblasts.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…These results provide evidence of the positive effect of onion extract on PON1 activity and prevention of LDL oxidation during periods of oxidative insult, with improvement in the antioxidant capability of rats, suggesting its value as a dietary antioxidant food . Moreover, quercetin has been previously shown to exert protective effects on ageing of specific tissues in mouse and other cellular models . Quercetin and its derivative, namely quercetin caprylate as a proteasome activator with antioxidant properties has been reported to influence cellular lifespan, survival and viability of Human foetal lung fibroblast, cell lines derived from a 16–18 week old human foetus (HFL‐1) primary human fibroblasts.…”
Section: Discussionmentioning
confidence: 67%
“…44,46 Moreover, quercetin has been previously shown to exert protective effects on ageing of specific tissues in mouse and other cellular models. 47 Quercetin and its derivative, namely quercetin caprylate as a proteasome activator with antioxidant properties has been reported to influence cellular lifespan, survival and viability of Human foetal lung fibroblast, cell lines derived from a 16-18 week old human foetus (HFL-1) primary human fibroblasts. Moreover, when these compounds were supplemented to senescent fibroblasts, a rejuvenating effect was observed.…”
Section: Discussionmentioning
confidence: 99%
“…enhancement of exploratory behavior, spatial learning and memory has been revealed in aged mice (Liu et al, 2006), a protective effect on immune cell functions has been shown in prematurely senescent mice (Alvarez et al, 2006), whereas a reversal of ageing and chronic ethanol-induced cognitive dysfunction (Singh et al, 2003) and a protective effect in primary neurons against Abeta(1-42) (Ansari et al, 2009) have been also reported. Additionally, QUER has been shown to increase oxidative stress resistance and longevity in Saccharomyces cerevisiae (Belinha et al, 2007) and to extend lifespan in C. elegans (Kampkötter et al, 2007, Pietsch et al, 2009, Saul et al, 2008.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Rutin and quercetin improved spatial memory impairment and neuroprotective effects using the 8-arm radial maze task and Morris water maze (Liu et al, 2006;Pu et al, 2007). ROS has been proposed to be involved in neuronal apoptosis, and Pycnogenol ® scavenges free radicals and promotes cellular health (Peng et al, 2002;Siler-Marsiglio et al, 2004).…”
Section: Effect Of Pycnogenol ® On Memory Functionmentioning
confidence: 99%